Acceptability and Validity of the EQ-5D in Patients Living With Dementia - Michalowsky, Bernhard; Xie, Feng; Kohlmann, Thomas; Gräske, Johannes; Wübbeler, Markus; Thyrian, Jochen René; Hoffmann, Wolfgang (Value in health, 2020)
To assess the acceptability and validity of the 3 levels of the EQ-5D (EQ-5D-3L) compared with the Quality of Life in Alzheimer’s Diseases (QoL-AD) in patients living with dementia. The analysis was based on 560 dyads of persons with dementia and their caregivers of the multicenter observational study of dementia care networks in Germany (DemNet-D). Health-related quality of life was assessed by face-to-face interviews using the EQ-5D-3L (self-rating) and the QoL-AD (self- and proxy-rating). The number of missing values, the score ranges (observed vs possible range) and the floor and ceiling effects were used to assess the acceptability. We used one-way analyses of variance and multivariate linear regression models to evaluate the discriminative ability. The convergent validity was assessed using Spearman's correlation coefficient (rs) and multivariate regression models. The EQ-5D index had a higher response rate (89% vs 84%) and a comparable floor (>1%) but a higher ceiling effect (18% vs >1%) compared with the QoL-AD. Both measures can significantly differentiate between different stages of general health, instrumental activities of daily living, and depression. The EQ-5D index and the visual analog scale self-rating scores strongly correlated with the QoL-AD self-rating (rs = 0.644 and 0.553, respectively) but not with the proxy-rating score (rs = 0.314 and rs = 0.170, respectively), which was confirmed by multivariate regression analyses. The results satisfy acceptability, discriminative ability, and convergent validity for moderately cognitively and functionally impaired patients living with dementia. The EQ-5D-3L performed comparably with the QoL-AD, and could, therefore, be used in economic evaluations in dementia. The differences between self- and proxy-ratings should be evaluated and considered in the interpretation of health-related quality of life scores.